2020
DOI: 10.1007/s10557-020-07071-0
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines and Chemokines as Therapeutic Targets in Heart Failure

Abstract: Heart failure exhibits remarkable pathophysiologic heterogeneity. A large body of evidence suggests that regardless of the underlying etiology, heart failure is associated with induction of cytokines and chemokines that may contribute to the pathogenesis of adverse remodeling, and systolic and diastolic dysfunction. The pro-inflammatory cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1, and IL-6 have been extensively implicated in the pathogenesis of heart failure. Inflammatory cytokines modulate phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
198
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(212 citation statements)
references
References 151 publications
(173 reference statements)
5
198
1
8
Order By: Relevance
“…In particular, stimulation of cardiomyocytes with TNFα resulted in a negative inotropic action by alteration of calcium homeostasis or in an activation of apoptotic response by binding of TNFα to TNF receptor I (TNFRI) [ [33] , [34] , [35] ]. Moreover, the chronic stimulation of cardiac fibroblast with TNFα can destroy the balance among the synthesis and the release of matrix metalloproteinase and their inhibitors carried out to extracellular matrix (ECM) degradation and cardiac remodeling [ [33] , [34] , [35] , [36] ]. Moreover, the pro-inflammatory cytokine IL-1 β demonstrated a negative inotropic effect much stronger than TNFα alteration of calcium homeostasis and destruction of the β-adrenergic receptor [ 36 ].…”
Section: Cardiovascular Disease Is a Common Complication In Covid-19 mentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, stimulation of cardiomyocytes with TNFα resulted in a negative inotropic action by alteration of calcium homeostasis or in an activation of apoptotic response by binding of TNFα to TNF receptor I (TNFRI) [ [33] , [34] , [35] ]. Moreover, the chronic stimulation of cardiac fibroblast with TNFα can destroy the balance among the synthesis and the release of matrix metalloproteinase and their inhibitors carried out to extracellular matrix (ECM) degradation and cardiac remodeling [ [33] , [34] , [35] , [36] ]. Moreover, the pro-inflammatory cytokine IL-1 β demonstrated a negative inotropic effect much stronger than TNFα alteration of calcium homeostasis and destruction of the β-adrenergic receptor [ 36 ].…”
Section: Cardiovascular Disease Is a Common Complication In Covid-19 mentioning
confidence: 99%
“…Moreover, the chronic stimulation of cardiac fibroblast with TNFα can destroy the balance among the synthesis and the release of matrix metalloproteinase and their inhibitors carried out to extracellular matrix (ECM) degradation and cardiac remodeling [ [33] , [34] , [35] , [36] ]. Moreover, the pro-inflammatory cytokine IL-1 β demonstrated a negative inotropic effect much stronger than TNFα alteration of calcium homeostasis and destruction of the β-adrenergic receptor [ 36 ]. This cytokine can contribute also to apoptosis activation in cardiomyocytes and collagen synthesis in fibroblasts resulting in cardiac fibrosis [ 36 ].…”
Section: Cardiovascular Disease Is a Common Complication In Covid-19 mentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating levels of NT-proBNP, and also diastolic dysfunction have been reported to be increased in AA patients without clinical HF compared to control individuals without AA or other inflammatory diseases [ 15 18 ]. This might reflect the presence of subclinical cardiac stress and increased myocardial wall tension, which may contribute to HF progression, due to increased secretion of BNP in cardiomyocytes, induced by proinflammatory cytokines [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that atherosclerosis is a chronic vascular wall-related inflammatory disease that occurs within the arterial wall ( 2 ). Inflammatory factors are mainly divided into three categories: i) Chemokines, including monocyte chemoattractant protein-1 (MCP-1), fractalkine/CX3CR1 and macrophage colony stimulating factor, whose effects are inhibited by macrophage migration inhibition factor (MIF); ii) pro-inflammatory factors, including C-reactive protein, IL-6, IL-1 and TNF-α; and iii) anti-inflammatory factors, including IL-10 and TGF-β ( 3 ). Pharmacological studies have reported that the imbalances between the pro-atherogenic inflammatory response and atheroprotective anti-inflammatory responses serve a key role in the initiation and progression of atherosclerosis ( 4 ).…”
Section: Introductionmentioning
confidence: 99%